Expert consensus on a multidisciplinary approach for the management of multiple myeloma-related bone disease - Yutong Wang; Qiming Xu; Yuan Li; Yongbin Su; Ling Wang; Xiaoquan Wang; Jian Ge; Hongmei Jing; Yuxing Guo; Yalin Chen; Xianan Li; Jun-ling Zhuang; et al. (Cancer Pathogenesis and Therapy, 2025)
This consensus on multiple myeloma-related bone diseases (MBDs) underscores the importance of a multidisciplinary approach that encompasses hematology, radiology, orthopedics, and additional specialties to tackle its intricate challenges. MBD, a prevalent and debilitating complication of multiple myeloma, leads to bone pain, fractures, and skeletal-related events (SREs), which profoundly impact patients’ quality of life. The guidelines offer a thorough framework for diagnosis, treatment, and continual assessment, emphasizing early detection and consistent monitoring using imaging techniques such as positron emission tomography-computed tomography (PET-CT) and magnetic resonance imaging (MRI). Treatment strategies prioritize the careful application of anti-myeloma agents, bisphosphonates, and denosumab to minimize bone loss and decrease SRE risk, complemented by surgical and radiotherapy interventions for structural or pain-related issues. Supportive care measures, including pain management, rehabilitation, nutritional support, and dental evaluations, play a crucial role in enhancing patient outcomes and preserving quality of life. This consensus advocates a standardized, evidence-based approach to managing MBD, ensuring comprehensive and coordinated care for patients.